Modulator-Mediated Functionalization of MOF-808 as a Platform Tool to Create High-Performance Mixed-Matrix Membranes - Thür, Raymond; Van Velthoven, Niels; Lemmens, Vincent; Bastin, Maarten; Smolders, Simon; De Vos, Dirk; Vankelecom, Ivo F J (ACS applied materials & interfaces, 2019)
Modulator-mediated functionalization (MoFu) is introduced as a new and versatile platform tool to improve the separation performance of metal-organic framework (MOF)-based membranes, exemplified here by the creation of mixed-matrix membranes (MMMs) with enhanced CO2 separation efficiency. The unique structure of MOF-808 allows incorporation of CO2-philic modulators in the MOF framework during a one-pot synthesis procedure in water, thus creating a straightforward way to functionalize both MOF and corresponding MMM. As a proof of concept, a series of fluorinated carboxylic acids [trifluoroacetic acid (TFA), pentafluoropropionic acid (PFPA), and heptafluorobutyric acid (HFBA)] and nonfluorinated alkyl carboxylic acids (acetic acid (AA), propionic acid (PA), and butyric acid (BA)) were used as a modulator during MOF-808 synthesis. Two of the best MMMs prepared with 30 wt % MOF-TFA (100% increase in CO2/CH4 separation factor, 350% increase in CO2 permeability) and 10 wt % MOF-PFPA (140% increase in CO2/CH4 separation factor, 100% increase in CO2 permeability) scored very close to or even crossed the 2008 and 2018 upper bound limits for CO2/CH4. Because of its facile functionalization (and its subsequent excellent performance), MOF-808 is proposed as an alternative for widely used UiO-66, which is, from a functionalization point-of-view and despite its widespread use, a rather limited MOF.Modulator-mediated functionalization (MoFu) is introduced as a new and versatile platform tool to improve the separation performance of metal-organic framework (MOF)-based membranes, exemplified here by the creation of mixed-matrix membranes (MMMs) with enhanced CO2 separation efficiency. The unique structure of MOF-808 allows incorporation of CO2-philic modulators in the MOF framework during a one-pot synthesis procedure in water, thus creating a straightforward way to functionalize both MOF and corresponding MMM. As a proof of concept, a series of fluorinated carboxylic acids [trifluoroacetic acid (TFA), pentafluoropropionic acid (PFPA), and heptafluorobutyric acid (HFBA)] and nonfluorinated alkyl carboxylic acids (acetic acid (AA), propionic acid (PA), and butyric acid (BA)) were used as a modulator during MOF-808 synthesis. Two of the best MMMs prepared with 30 wt % MOF-TFA (100% increase in CO2/CH4 separation factor, 350% increase in CO2 permeability) and 10 wt % MOF-PFPA (140% increase in CO2/CH4 separation factor, 100% increase in CO2 permeability) scored very close to or even crossed the 2008 and 2018 upper bound limits for CO2/CH4. Because of its facile functionalization (and its subsequent excellent performance), MOF-808 is proposed as an alternative for widely used UiO-66, which is, from a functionalization point-of-view and despite its widespread use, a rather limited MOF.